Understanding older adults' intention to use patient-accessible electronic health records: Based on the affordance lens - Wang, Xindi; Zhao, Yuxiang Chris (Frontiers in Public Health, 2023)
Background Given the aging population and the rapid development of the digital society, concerns about promoting older adults' health skills are increasing. Patient-accessible electronic health records (PAEHRs) are implemented globally for aging health safeguards. The demand for using health-related information communication technologies (ICTs) among older adults and the factors that promote their usage intention of PAEHRs need to be studied. Methods Drawing upon affordance theory, we constructed a research model that integrates four affordance types, aggregation, interactivity, collaboration, and communication, to identify the effects of affordances and attachment to platforms and doctors that contribute to older adults' usage intention on PAEHRs. Online survey data from 498 older adults (above 60 years) were collected and analyzed using partial least square-structural equation modeling. Results Our findings demonstrated how PAEHR's affordances facilitate older adults' attachment to platforms and doctors. We found that aggregation (γ = 0.417, P < 0.001) and interactivity (γ = 0.397, P < 0.001) can positively influence older adults' attachment to the PAEHR platform, and collaboration (γ = 0.407, P < 0.001) affordance can positively influence older adults' attachment to doctors on the PAEHR platform. Furthermore, seniors' attachment to the platform (γ = 0.598, P < 0.001) and attachment to the doctor (γ = 0.156, P < 0.01) can both positively influence their usage intention, and attachment to the platform had a positive relationship with attachment to doctors (γ = 0.230, P < 0.001) on the PAEHR. Conclusion This study enriched the understanding of elders' attachment to doctors on PAEHRs and contributed to the literature on health-related ICT usage targets of older adults. Our findings also shed light on inspiring operators of health-related ICTs to formulate appropriate strategies for aging-friendly design to guide older adults to adopt health-related ICTs in their everyday health information practices.